1953
DOI: 10.1017/s002217240001545x
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the food preferences of wild rats (Rattus norvegicusBerkenhout)

Abstract: 1. Colonies of wild Rattus norvegicus Berkenhout were kept in closed rooms containing nesting sites. The conditions permitted breeding.2. Seventy-six experiments, each lasting 6–35 days, were done to test the rats' food preferences. In each experiment except two, a choice was given between two foods, both available in excess. In the two exceptional experiments a choice between three foods was given.3. Although marked preferences were shown, a food was rarely quite rejected in favour of an alternative.4. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1953
1953
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…Nile rat responses to groundnut oil were similar to those shown by Philippine rice rats (R. r. mindanensis) (Kuehnert, 1976). In contrast, Norway rats have been shown to increase acceptance when wheat or whole meal was treated with groundnut oil (Barnett and Spencer, 1953). We should emphasise that Nile rats may have preferences for other vegetable oils even though groundnut oil tended to be rejected by the animals in our study.…”
Section: Laboratory Testscontrasting
confidence: 58%
See 2 more Smart Citations
“…Nile rat responses to groundnut oil were similar to those shown by Philippine rice rats (R. r. mindanensis) (Kuehnert, 1976). In contrast, Norway rats have been shown to increase acceptance when wheat or whole meal was treated with groundnut oil (Barnett and Spencer, 1953). We should emphasise that Nile rats may have preferences for other vegetable oils even though groundnut oil tended to be rejected by the animals in our study.…”
Section: Laboratory Testscontrasting
confidence: 58%
“…We should emphasise that Nile rats may have preferences for other vegetable oils even though groundnut oil tended to be rejected by the animals in our study. Many reports (Crabb and Emik, 1946;Barnett and Spencer, 1953;Shumake, 1978) have indicated that rats of a given species will show varying degrees of preference for certain oils added to their food.…”
Section: Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding behaviour of rats and mice flour (75 % extraction) took very little of the wheat germ and fed almost entirely on the flour (Barnett & Spencer, 1953). These observations are also against the explanation of the choice being due to nutritional value.…”
Section: Discussionmentioning
confidence: 98%
“…This would suggest that the palatability of the food was decreased duo to additives. This is a paradoxical situation because in many other rodents (•attus norvegicus; (Barnett and Spencer, 1953) and Rattus rattus (Khan 19 74) these additives have B K Son~, I Prakash and R P Mathur been found to have increased the consumption of the test foods. This observation may, however, indicate that due to these additives when the calori~c value of the food iazreases, their intake increases.…”
Section: Tastementioning
confidence: 99%